Improved response of human gingival fibroblasts to titanium coated with micro-/nano-structured tantalum - Chu-nan Zhang (International Journal of Implant Dentistry, 2021)
Abstract Objectives This study aims to evaluate the ability of tantalum-coated titanium to improve human gingival fibroblasts’ adhesion, viability, proliferation, migration performance, and the potential molecular mechanisms. Materials and methods Titanium plates were divided into two groups: (1) no coating (Ti, control), (2) Tantalum-coated titanium (Ta-coated Ti). All samples were characterized by scanning electronic microscopy, surface roughness, and hydrophilicity. Fibroblasts’ performance were analyzed by attached cell number at 1 h, 4 h, and 24 h, morphology at 1 h and 4 h, viability at 1 day, 3 days, 5 days, and 7 days, recovery after wounding at 6 h, 12 h, and 24 h. RT-PCR, western blot were applied to detect attachment-related genes’ expression and protein synthesis at 4 h and 24 h. Student’s t test was used for statistical analysis. Results Tantalum-coated titanium demonstrates a layer of homogeneously distributed nano-grains with mean diameter of 25.98 (± 14.75) nm. It was found that after tantalum deposition, human gingival fibroblasts (HGFs) adhesion, viability, proliferation, and migration were promoted in comparison to the control group. An upregulated level of Integrin β1 and FAK signaling was also detected, which might be the underlying mechanism. Conclusion In the present study, adhesion, viability, proliferation, migration of human gingival fibroblasts are promoted on tantalum-coated titanium, upregulated integrin β1 and FAK might contribute to its superior performance, indicating tantalum coating can be applied in transmucosal part of dental implant. Clinical significance Tantalum deposition on titanium surfaces can promote human gingival fibroblast adhesion, accordingly forming a well-organized soft tissue sealing and may contribute to a successful osseointegration.